The Influence Of Carbon Accounting Disclosure And Audit Quality On Corporate Efficiency In Industrial Sector Companies Listed On The Indonesia Stock Exchange - Maf’ul Taufiq; Weny Ananda Putri; Mifthahul Jannah; Imanuela Aprilia Rajagukguk (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the impact of carbon accounting disclosure and audit quality on corporate efficiency within the industrial sector listed on the Indonesia Stock Exchange (IDX), as well as to examine the moderating role of audit quality in the relationship between carbon disclosure and corporate efficiency. Growing global attention toward sustainability and climate change issues has prompted companies to enhance carbon emission transparency and strengthen oversight mechanisms through high-quality audits. This study employs a quantitative approach with an explanatory research design. Secondary data were obtained from the annual and sustainability reports of industrial sector companies listed on the IDX for the 2019–2023 period. The sample was selected using a purposive sampling technique. Corporate efficiency was measured using Data Envelopment Analysis (DEA) and the Total Asset Turnover (TATO) ratio; carbon accounting disclosure was measured using the Carbon Disclosure Index (CDI) based on GRI/CDP standards; and audit quality was proxied by a dummy variable (Big Four vs. non-Big Four). Data analysis was conducted using multiple panel regression and moderated regression analysis (MRA). The results indicate that: (1) carbon accounting disclosure has a positive and significant effect on corporate efficiency; (2) audit quality has a positive and significant effect on corporate efficiency; and (3) audit quality strengthens the relationship between carbon accounting disclosure and corporate efficiency. This study supports legitimacy theory, stakeholder theory, and signaling theory, and contributes to the sustainability accounting literature in Indonesia.